Knowledge, Attitude, and Practice of HPV (Human Papilloma Virus) Vaccine among Health Care Professionals of RMU and Allied Hospitals: A Cross-Sectional Study - Sharjeel Ashraf, Muhammad; Rasheed, Fatima; Khurshid, Qandeel; Hassan, Zohaib; Saleem, Maimoona; Bilal, Sana (Students' Supplement of Journal of Rawalpindi Medical College, 2024)
Introduction: Cervical cancer, usually caused by HPV, is becoming a serious health risk and an emerging cause of death among women worldwide. More than 60 million females are at risk in Pakistan alone. Vaccination against HPV is one of the most effective methods to combat the issue but might yet be largely unknown in developing nations owing to its newness, and a thorough understanding of medical professionals’ awareness of it is lacking. Objectives: The objectives of this study are to assess the health professionals’ knowledge of HPV, their awareness of the HPV vaccine, and their attitudes and practices associated with it. Materials and Methods: A cross-sectional survey involving 278 medical practitioners from Allied hospitals. Participants were recruited using convenience sampling and their responses were gathered via a self-administered standardized questionnaire. The analysis was done using SPSS v27 to provide descriptive details, determine associations using chi-square tests and correlation analysis, and ascertain differences among categories using ANOVA. Results: Many gaps and misconceptions were found about knowledge of the HPV vaccine. Only 47.5% were aware of the existence of the HPV vaccine in Pakistan, with numerous misconceptions about the target group. Despite these knowledge gaps, and though, only 6.5% of the professionals were vaccinated themselves, 64.8% expressed confidence in the vaccine's effectiveness, and 76.3% were willing to vaccinate their children. Conclusion: The study revealed a satisfactory level of knowledge regarding HPV among doctors, but it was somewhat lacking in the case of nurses and paramedics. Significant gaps in awareness about HPV vaccination and its practices were identified. Tailored interventions, increased affordability, and comprehensive education campaigns are pivotal to bridging these gaps and informed vaccination practices should be advocated